O Serviço Social e conhecimento: a relação teoria-prática: https://doi.org/10.60543/ts_iss.vi6.9290 ("Temas Sociais" Journal, 2024)
Social Work, intrinsically linked to professional theories and practices, requires an in-depth understanding of the theoretical basis underlying its operationalization. Social changes encourage the production of epistemological knowledge that adapts to new trends and paradigms of intervention centered on the person and context. The search for theory underpins evidence-based practice, considering several social dimensions. In addition to practical intervention, the instrumental dimension of the profession incorporates theoretical knowledge to adjust methodologies and interpret social reality.
Keywords: Social services; Knowledge; Intervention; Evidence.